Occupational stress among community health workers in a rural field practice area of Belagavi - R, Sriram T; Kulkarni, Rajesh; Bellad, Asha; Wali, Abhinandan (Indian Journal of Community Health, 2023)
Introduction: Community health workers (CHW) are the first level of contact between the health system and the community. This study aimed to find out the level and areas of occupational stress among CHWs so that they can be addressed accordingly. Methods: This study was carried out among 105 CHWs in a rural field practice area of Belagavi. A pre-tested, structured, standard questionnaire was provided to them. After obtaining informed consent, they were asked to fill in the questionnaire. The collected data was entered and analysed through SPSS Version 26. Results: The mean age of the participants was 41.91 years. Majority were Hindu (79.1%). Most of the participants had completed high school (51.4%). 25.7% of the participants belonged to socioeconomic class IV, 34.3% said that theirs is the only income in the family, and 22.9% said that salary is the motivation for them to continue working. Among the participants, 16.19% had low stress, 80.95% moderate stress, and 2.85% high stress. The major area of stress was role overload (18.3%). Conclusion: CHWs are vital for the efficient functioning of primary health services at community level and their role in healthcare and the delivery of various national health programmes is indispensable, so their health and proper work environment should be ensured and safeguarded.